(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The harmful effects of spent engine oil on aquatic and terrestrial ecosystems have been well established in literature. This study was conducted to assess the bio stimulatory influence of amendments; compost and inorganic fertilizer on bacterial degradation of spent engine oil contaminated soil. 500 g of unpolluted soil was collected and artificially contaminated with 5, 10 and 15% (v/w) spent engine oil. The experiment was laid out in a completely randomized design. Each amendment (50 g) was subsequently mixed thoroughly with the spent engine oil contaminated soil at varying levels except nine experimental bottles used as control. Incubation study was carried out and lasted for four weeks. Estimation of total petroleum hydrocarbon, pH, electrical conductivity, temperature and bacterial population density was done within two weeks interval during the incubation study. Results obtained indicate that compost significantly enhanced total petroleum hydrocarbon reduction by 87% while inorganic fertilizer facilitated 62% total petroleum hydrocarbon reduction on 5% spent engine oil contamination level respectively. Estimation of hydrocarbon utilizing bacteria on 5, 10 and 15% spent engine oil contaminated soil indicated that compost enhanced higher hydrocarbon utilizing bacteria thereby influencing bacterial degradation than those stimulated with inorganic fertilizer. pH remained in the range of alkalinity (7.8 and 8.06) for compost and 6.2 and 6.7 for inorganic fertilizer. The potential that compost recorded in influencing bacterial degradation of spent engine oil contaminated soil in this study has made it a good bio stimulant for the bioremediation of hydrocarbon polluted environments.